2021
DOI: 10.3390/j4030028
|View full text |Cite
|
Sign up to set email alerts
|

Pyoderma Gangrenosum: A Review of Updates in Diagnosis, Pathophysiology and Management

Abstract: Pyoderma gangrenosum (PG) is a rare entity that is characterized by infiltration of neutrophils into the dermis, causing the formation of rapidly enlarging, painful and necrotic skin ulcers. The pathophysiology of PG is still poorly understood. However, genetic, autoimmune and autoinflammatory mechanisms have been proposed that could potentially explain the etiology of this ulcerating skin disorder. Early diagnosis and treatment are key, as the disease course is rapidly progressive and can leave disfiguring, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 41 publications
0
25
1
1
Order By: Relevance
“…It has been well documented in the literature that pyoderma gangnosum is usually associated to many different diseases such as inflammatory bowel disease, autoimmune diseases, and hematologic malignancies [1,4,7,8] but in our case we did not find any other diseases associated to PG.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…It has been well documented in the literature that pyoderma gangnosum is usually associated to many different diseases such as inflammatory bowel disease, autoimmune diseases, and hematologic malignancies [1,4,7,8] but in our case we did not find any other diseases associated to PG.…”
Section: Discussioncontrasting
confidence: 72%
“…, the international Delphi Criteria and PARACELSUS score in 2018, all had major and minor criteria but in 2021 a cross-sectional retrospective cohort study found that the PARACELSUS score was the most accurate and precise tool to use in the diagnosis of PG [7].…”
Section: Discussionmentioning
confidence: 99%
“…PG is often associated with systemic diseases, such as rheumatoid arthritis, inflammatory bowel disease, and other autoimmune and inflammatory diseases 2 . While the exact pathophysiologic mechanisms of PG remain unclear, autoimmune processes driven by abnormalities in the innate immune system are implicated 2 . Unlike conventional PG, vaccination‐associated PG presents without associated systemic diseases 3 .…”
Section: Figurementioning
confidence: 99%
“… 2 While the exact pathophysiologic mechanisms of PG remain unclear, autoimmune processes driven by abnormalities in the innate immune system are implicated. 2 Unlike conventional PG, vaccination‐associated PG presents without associated systemic diseases. 3 In our case, it is highly likely that COVID‐19 vaccination could have contributed to the development of PG due to their close temporal relationship.…”
mentioning
confidence: 99%
“…Reumatologia 2022; 60/4 cular occlusive or venous disease, skin cancer, infection, or drug reaction, are excluded. There are 3 systems of criteria -Mayo, Delphi Consensus, and PARACELSUS-score, among which the latter appears to be the most valuable [10].…”
mentioning
confidence: 99%